2022
DOI: 10.6004/jnccn.2021.7059
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Outcomes of Patients With BRAF-Mutated Metastatic Colorectal Cancer Treated in the United States

Abstract: Background: BRAF mutations portend a poor prognosis in metastatic colorectal cancer (mCRC). Whether these patients may benefit from more aggressive frontline chemotherapy with a triplet regimen such as FOLFOXIRI remains unclear. We used real-world data from a cohort of patients in the United States to assess the BRAF testing rate, determine the prevalence of FOLFOXIRI use, and compare survival outcomes in mCRC, stratified by BRAF mutation status and first-line therapy. Methods: A nationwide electronic health r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Identification of these markers may allow patient stratification to reduce toxicity, costs, and potentially allocate non-responder patients to other treatment approaches. In addition, the applicability of new and complex treatment regimens, as observed for e.g., FOLFOXIRI and VEGF- or anti-EGFR-antibodies ( 25 ), may be hampered in mCRC due to the high response rates of the backbone chemotherapy alone and response predicting markers may allow clinical stratification of patients. If asked to speculate, this may be especially important for patients who are in need of maximal response to treatment to achieve a potential secondary resection.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of these markers may allow patient stratification to reduce toxicity, costs, and potentially allocate non-responder patients to other treatment approaches. In addition, the applicability of new and complex treatment regimens, as observed for e.g., FOLFOXIRI and VEGF- or anti-EGFR-antibodies ( 25 ), may be hampered in mCRC due to the high response rates of the backbone chemotherapy alone and response predicting markers may allow clinical stratification of patients. If asked to speculate, this may be especially important for patients who are in need of maximal response to treatment to achieve a potential secondary resection.…”
Section: Discussionmentioning
confidence: 99%
“…Also, a meta-analysis of 11 prospective and retrospective studies of liver resection reported that KRAS mt and BRAF mt mutational status was negatively associated with OS and relapse-free survival (RFS) [ 9 ]. Also, a recent retrospective real-world study from US reported worse survival for BRAF mt mCRC patients compared to BRAF wt [ 34 ]. The worse outcome in RAS mt and BRAF mt is probably due to both the mutations and right-sided primary according to multivariable analysis.…”
Section: Discussionmentioning
confidence: 99%